2001
DOI: 10.1007/s004210100458
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive cardiac output evaluation during a maximal progressive exercise test, using a new impedance cardiograph device

Abstract: One of the greatest challenges in exercise physiology is to develop a valid, reliable, non-invasive and affordable measurement of cardiac output (CO). The purpose of this study was to evaluate the reproducibility and accuracy of a new impedance cardiograph device, the Physio Flow, during a 1-min step incremental exercise test from rest to maximal peak effort. A group of 12 subjects was evaluated to determine the reproducibility of the method as follows: (1) each subject performed two comparable tests while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
2
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(180 citation statements)
references
References 9 publications
6
164
2
6
Order By: Relevance
“…Stroke volume was measured by bioimpedance, whereas heart rate was simultaneously estimated from the electrocardiogram first derivative (Manatec type PF05L1; Physio Flow, Paris, France). The accuracy of this bioimpedance device has previously been established against the direct Fick method during maximal incremental exercise in healthy subjects (36). Calibration of the impedance device was done using a procedure based on 24 consecutive heartbeats recorded with the subject resting on the ergometer (10).…”
Section: Methodsmentioning
confidence: 99%
“…Stroke volume was measured by bioimpedance, whereas heart rate was simultaneously estimated from the electrocardiogram first derivative (Manatec type PF05L1; Physio Flow, Paris, France). The accuracy of this bioimpedance device has previously been established against the direct Fick method during maximal incremental exercise in healthy subjects (36). Calibration of the impedance device was done using a procedure based on 24 consecutive heartbeats recorded with the subject resting on the ergometer (10).…”
Section: Methodsmentioning
confidence: 99%
“…Stroke volume (SV) was estimated beat by beat by impedence cardiography (Physio Flow, Manatec, Paris, France) (33). The accuracy of this device has been previously evaluated during incremental exercise in healthy subjects against the direct Fick method (33); in that study, the correlation coefficient between the two methods was r ϭ 0.946 (P Ͻ 0.01), and the mean difference was equal to Ϫ2.78 Ϯ 12.33% (2 SD). Overall, the accuracy of this method can be considered "acceptable" for the purpose of the study, which is to demonstrate that the cardiac involvement during KE was not "maximal" also at peak exercise (as confirmed also from HR measurements).…”
Section: Measurementsmentioning
confidence: 99%
“…The algorithm that is used does not require basal thoracic impedance measurement or the estimation of blood resistivity and the position of the electrodes is not critical for the accuracy of the measurements. Previous studies showed that Physioflow provides accurate cardiac output measurements during steady-state and maximal exercise in healthy subjects (8,34). However, in patients with chronic obstructive pulmonary disease (COPD), cardiac output was systematically overestimated (7).…”
mentioning
confidence: 99%